1998
DOI: 10.4269/ajtmh.1998.59.633
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcal colonization in a developing country: its association with sexually transmitted disease and socioeconomic factors.

Abstract: Abstract. Group B Streptococcus (GBS) is an important infectious organism in pregnant women and their neonates. Although excellent data are available from the developing world, little epidemiologic information is available from Latin America. To evaluate the prevalence of GBS colonization in a developing country, a prospective study was performed in Lima, Peru. We found a relatively low prevalence of GBS colonization of 6.0% in parturient women and 10.6% in nonpregnant women. No association of GBS colonization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
4
21
1
1
Order By: Relevance
“…16 With regard to the group B streptococcal infection, a study from Peru reported a prevalence of 6%; and another study in the United States reported an even higher 18.6%. 17,18 Although the prevalence of the two infections in Nghe An Province was relatively low when compared with the ones reported in the aforementioned studies, these two are known as strong risk factors for preterm delivery and neonatal infection. 19,20 The reviews by the Cochrane Collaboration and the WHO recommend that high-risk women with a history of preterm delivery be screened for bacterial vaginosis.…”
Section: Discussionmentioning
confidence: 78%
“…16 With regard to the group B streptococcal infection, a study from Peru reported a prevalence of 6%; and another study in the United States reported an even higher 18.6%. 17,18 Although the prevalence of the two infections in Nghe An Province was relatively low when compared with the ones reported in the aforementioned studies, these two are known as strong risk factors for preterm delivery and neonatal infection. 19,20 The reviews by the Cochrane Collaboration and the WHO recommend that high-risk women with a history of preterm delivery be screened for bacterial vaginosis.…”
Section: Discussionmentioning
confidence: 78%
“…Não houve, conforme os resultados obtidos, em concordância com a maioria das pesquisas, como correlacionar DST e colonização pelo EGB 10,21 . No sentido inverso, estão os achados de maior prevalência em mulheres com freqüência maior de relações sexuais por semana e mais de um parceiro sexual, inclusive com resultados estatisticamente significativos quando estas duas variá-veis foram comparadas em relação ao restante da amostra, como já foi citado anteriormente, indicando a promiscuidade como um fator importante na colonização.…”
Section: Discussionunclassified
“…In previous studies, the prevalence indexes for GBS in Brazil (14.6% to 32.6%) [13][14][15][16][17] were similar to those in countries that have adopted universal laboratory screening and maternal intrapartum antibiotic prophylaxis (10% to 30%); however, these values could potentially vary greatly by geographic location, sociodemographic and clinical characteristics, and the detection technique employed.…”
Section: Tablementioning
confidence: 99%
“…This colonization is a dynamic condition and represents the main risk factor for early neonatal infection. Notably, the international literature reports maternal GBS colonization rates of 6.5-36.0% in Europe 6,7 , 10.0-30.0% in North America 2,8 , 16.5-31.6% in African countries 9 , and 1.4-36.7% in South America, including Brazil [10][11][12][13] , Chile 14 , Peru 15 , and Argentina 16 .…”
Section: Introductionmentioning
confidence: 99%